Domination of Woman in the Selected Novel of Margaret Eleanor Atwood: Exploring Gender Struggles and Self-Identity in Margaret Atwood's The Edible Woman (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women's liberation is both a scholarly responsibility and a political development that quest for equity for lady and the end of sexism in all forms. The rule lady ought to be dealt with equivalent to man. And furthermore, it is any demonstrations or deeds, particularly sorted out, that urge women's rights to move towards correspondence with men. Marian Atwood's way of life as a Canadian writer has consistently been critical to her, and she made gigantic progress regardless of the genuine handicap exhibited by her craving to be known as a Canadian author. The Edible Woman is the principal distributed novel by Margaret Atwood. Wealthy in metaphor, deliciously comic, and glittering with understanding, the story chronicles the fantastic and dramatic sense of self deterioration of Marian McAlprin, who appears from the outset to be a consummately traditional girl, with friends, a fruitful and appealing man in her life, and a sensibly great job working for a market research company. Everything in her life appears to fly crazy with her commitment, similarly as Marian appears to be prepared to satisfy each woman's dream of exchanging her inconvenient job for marriage and another life at home with kids. The way of her breakdown and the frightening completion make for regularly diverting perusing. Edible Woman is the tale of a woman who starts recognizes the truth. Marian isn't deliberately a radical, nor does she consider herself strange in her expectations and desires. She fights herself so as to her internal identity. This paper manages the struggle between the job that society has forced upon her and her own meaning of self.